Implementation of Multicultural Education in Preventing Bullying Behavior among Early Childhood Children in Islamic Educational Institutions: A Case Study at TK NU Al Madani Wonosobo - Vava Imam Agus Faisal; Mahmud Arif; Muqowim Muqowim; Salis Wahyu Hidayati; Umi Latifah (Assyfa Journal of Islamic Studies, 2026)
Bullying behavior in early childhood can hinder children’s social, emotional, and character development; therefore, prevention efforts are required through education that instills values of tolerance, empathy, and respect for diversity. This study aims to describe the implementation of multicultural education in preventing bullying behavior among early childhood children at TK NU Al Madani. The research employs a qualitative approach with a case study design. The research subjects consist of the principal, teachers, and students, selected using purposive sampling technique. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The results show that the implementation of multicultural education is carried out through anti-bullying socialization using role-play methods, the use of educational videos, character building and reinforcement, as well as verbal approaches in learning. These activities foster attitudes of tolerance, empathy, and mutual respect, thereby supporting the prevention of bullying behavior. This study concludes that multicultural education integrated into learning and daily habits contributes to creating an inclusive, safe, and conducive learning environment for children’s social-emotional development